EFFECT OF CORPORATE GOVERNANCE AND TAX AVOIDANCE ON FIRM VALUE: CSR AS MODERATION - Ardha, Muhammad Zulfi; Prajawati, Maretha Ika; S, Basir (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to determine the effect of Corporate Governance and Tax Avoidance on Firm Value with CSR as a moderating variable in mining sector companies in Indonesia. This study uses a descriptive quantitative approach. The method used is multiple linear regression analysis and Moderate Regression Analysis (MRA) using 22 samples of mining sector companies listed on the IDX during the 2017-2021 period. The result of the study show that the Independent Board of Commissioners and Tax Avoidance have a positife effect on Firm Value, while Managerial Ownership has a negative effect on Firm Value. Futhermore, CSR can negative and significantly moderate the relationship between the Independent Board of Commissioners on Firm Value. In addition, CSR can also negatively moderate the relationship between Managerial Ownership and Firm Value. However, CSR cannot moderate the relationship between Tax Avoidance and Firm Value.